Using Syntectonic Calcite Veins to Reconstruct the Strength Evolution of an Active Low‐Angle Normal Fault, Woodlark Rift, SE Papua New Guinea. Issue 8 (11th August 2021) - Mizera, Marcel; Little, Tim; Boulton, Carolyn; Katzir, Yaron; Thiagarajan, Nivedita; Prior, David J.; Biemiller, James; Smith, Euan G. C.
Abstract: Quantifying the strength evolution of faults that cut the lithosphere is essential to better understand seismicity in continental regions. We estimate differential stresses and principal stress orientations driving rapid slip of ∼10 mm/yr on the active Mai'iu low‐angle normal fault (LANF), SE Papua New Guinea. The fault's mafic footwall hosts a well‐preserved sequence of mylonite, (ultra‐)cataclasite, and gouge. In these fault rocks, we combine stress inversion of fault‐slip data and paleostress analysis of syntectonically emplaced calcite veins with microstructural and clumped‐isotope geothermometry to constrain a syn‐exhumational sequence of deformation stresses and temperatures, and to construct a stress profile through the exhumed footwall of the active Mai'iu LANF. This includes: (a) at ∼12–20 km depth ( T ≈ 275–370°C), mylonites accommodated slip on the Mai'iu fault at low differential stresses (>25–135 MPa) before being overprinted by localized brittle deformation at shallower depths; (b) at ∼6–12 km depth ( T ≈ 130–275°C) differential stresses in the foliated cataclasites and ultracataclasites were high enough (>150 MPa) to drive slip on a mid‐crustal portion of the fault (dipping 30–40°), and to trigger brittle yielding of mafic footwall rocks in a zone of mixed‐mode seismic/aseismic slip; and (c) at shallower crustal depths ( T < 150°C; depth <6 km) on the most poorly oriented segment of the Mai'iu LANF (dipping ∼22°), slip occurred on frictionally weak clay‐rich gouges (μ ≈ 0.15–0.38). Subvertical σ1 and subhorizontal σ3 parallel to the extension direction, with σ1 ≈ σ2 (constriction), reflect vertical unloading and 3‐D bending strain during rolling‐hinge style flexure of the footwall. Key Points: High differential stresses drive slip on a 35° dipping part of the Mai'iu fault and cause brittle yielding of strong mafic footwall rocks A differential stress peak of 140–185 MPa at 6–12 km depth was identified in a zone of mixed‐mode seismic‐ and aseismic slip The Mai'iu fault is frictionally weak (μ ≈ 0.15–0.38) at shallow depth (<6 km) where it is a true low‐angle normal fault (dipping ∼22°)